A multi-shelled CoP nanosphere modified separator for highly efficient Li–S batteries. Issue 28 (10th July 2018) - Chen, Xiaoxia; Ding, Xuyang; Wang, Chunsheng; Feng, Zhenyu; Xu, Liqiang; Gao, Xue; Zhai, Yanjun; Wang, Debao
Abstract : Multi-shelled CoP nanospheres are designed as a new kind of coated separator material for highly efficient Li–S batteries, which exhibits outstanding cycling stability with a capacity degradation of 0.078% per cycle over 500 cycles at 1 C and also excellent rate performances. Abstract : Lithium–sulfur batteries are considered to be one of the most promising energy-storage systems because of their high theoretical energy density, as well as low cost, nontoxicity and natural abundance of sulfur. However, their poor cycling stability mostly originates from the shuttling of polysulfides which hinders their future practical applications. Here, multi-shelled CoP nanospheres are designed as a coated separator material for Li–S batteries for the first time. Conductive CoP can efficiently anchor polysulfides not only owing to its polar character but also its partial natural surface oxidation feature as evidenced by XPS results, which further activates Co sites for chemically trapping polysulfides via strong Co–S bonding. Furthermore, the unique multi-shelled structure can capture polysulfides to alleviate the "shuttle effect". Consequently, the battery using a CoP coated separator exhibits outstanding cycling stability with a capacity degradation of 0.078% per cycle over 500 cycles at a current density of 1 C and excellent rate performance (725 mA h g −1 at 5 C). It is also worth noting that a high areal capacity of 3.2 mA h cm −2 can be achieved even with a sulfur loading of 3.24 mg cm −2 . Our approach demonstrates the convenient fabrication and application potential for a multi-shelled CoP nanosphere modified separator for highly efficient Li–S batteries.